Optimun temperatures for Bermuda winter overseeding with cool-season grasses in the centre-south of Cordoba province, Argentina - Caminos, Teresa S. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The objectives were to determine average soil (TMS) and minimum air (TMA) temperatures more suitable for winter overseeding, Cynodon dactylon. (Bermuda) growth rate (TCC) to minimize competition with the overseeded species and behavior of various cool-season species in the centralsouth of Córdoba province. Winter seeding was done during 2010 and 2011, in a split plot design with five seeding dates (FS) every 15 days, from early March, with three genotypes: Lolium multiflorum cv Axcella, L. perenne and L. perenne cv Excel I. Temperatures were measured from March until the bermuda entered in dormancy, calculating TMA and TMS. Turfgrass overall quality, soil coverage and bermudagrass TCC were registered. The winter overseeding that achieves higher values of overall quality, soil coverage and lower bermuda's TCC were found with TMS between 18 to 21°C and TMA between 11.5 to 15.5°C. According to normal average values of the central-south of Cordoba, optimum temperatures are observed between the second decade of March and first of April. All three genotypes had similar behaviors regardless of the FS used.